2011
DOI: 10.1186/1471-2458-11-214
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic risk factors, physical activity and physical fitness in azorean adolescents: a cross-sectional study

Abstract: BackgroundThe prevalence of metabolic syndrome has increased over the last few decades in adolescents and has become an important health challenge worldwide. This study analyzed the relationships between metabolic risk factors (MRF) and physical activity (PA) and physical fitness (PF) in a sample of Azorean adolescents.MethodsA cross-sectional school-based study was conducted on 417 adolescents (243 girls) aged 15-18 from the Azorean Islands, Portugal. Height, weight, waist circumference, fasting glucose, HDL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
1
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 37 publications
4
55
1
9
Order By: Relevance
“…The proportion of adolescents in this study with low cardiorespiratory fitness may be a reflection of lower cardiorespiratory fitness levels observed worldwide. These data are alarming considering the exposure of young individuals to cardiovascular risk factors during adolescence7 and adulthood 8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of adolescents in this study with low cardiorespiratory fitness may be a reflection of lower cardiorespiratory fitness levels observed worldwide. These data are alarming considering the exposure of young individuals to cardiovascular risk factors during adolescence7 and adulthood 8…”
Section: Discussionmentioning
confidence: 99%
“…The low level of cardiorespiratory fitness is associated with increased cardiovascular risk factors and metabolic syndrome in young individuals,7 as well as to increased cardiovascular risk in adulthood 8. A meta-analysis showed that the overall risk of death from all causes or from cardiovascular disease was two-fold higher in individuals with low cardiorespiratory fitness levels, compared to those with high levels 8.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, epidemiological studies have shown decrease of at least 50% in the mortality indices amongst subjects with high scores of physical fitness compared to the ones less physically fit 7 . Specifically in young populations, higher physical fitness scores are associated with lower prevalence of risk factors which lead to cardiovascular diseases, reduction in total and abdominal adiposity as well as better bone and mental health condition [8][9][10][11][12][13][14] . Furthermore, scores of health-related physical fitness components are more straightly related to metabolic risks than habitual physical activity practice levels in youngsters at school age 8,11,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically in young populations, higher physical fitness scores are associated with lower prevalence of risk factors which lead to cardiovascular diseases, reduction in total and abdominal adiposity as well as better bone and mental health condition [8][9][10][11][12][13][14] . Furthermore, scores of health-related physical fitness components are more straightly related to metabolic risks than habitual physical activity practice levels in youngsters at school age 8,11,14 . Although many studies trying to describe health-related physical fitness of young populations of other countries have been found [15][16][17][18][19] , in Brazil these data are scarcer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation